Análise das distorções harmônicas: estudo de caso de um sistema industrial - Douglas Angelo Teixeira (2009)
This work presents an overview about harmonics indicators, equipment that generate these distortions and sensitive equipment to these disturbances in the electrical system. Some standards on harmonics are discussed; among them IEEE 519 and the Network Procedures ONS were used as reference for evaluating the measured signals and check the conditions of the installation. The harmonic filters are used to reduce the distortions caused by non-linear actions equipment. The designs these filters, the existing definitions, and the evaluation each filtertypes are present together with practical criteria for selection. The measurements in the electrical system were taken in the large industrialconsumer in order to identify harmonic injections this company on the concessionaire network. The energy measurements were installed in the secondary of the main transformers of the company and entry substation to obtain these data. After the work data collection the electrical system was modeled on Simulink / Matlab. It simulation a simplified model of the electrical network including power from the concessionaire, transmission and distribution lines, the main transformers, loads and harmonics present in each of the feeders. From the analysis of the company seeks to propose improvements to enable to operate without harming the system that is connected and attend the limits of harmonic voltage distortion, recommended by the ONS and the power factor.